Formation interval determination method of MPD based on risk aversion and casing level optimization - Xu, Yuqiang; Han, Chao; Sun, Jiarui; He, Baolun; Guan, Zhichuan; Zhao, Yishu (Frontiers in Physics, 2022)
MPD is one of the effective means to solve the drilling problems in deep-water and deep-stratum complex formations such as narrow pressure window. To reduce the cost, it is mostly implemented only in complex and narrow pressure window strata. However, at present, there is no scientific method to determine the MPD matching stratum interval under the “conventional + MPD” composite drilling mode. Aiming at this problem, by introducing the methods of risk quantitative evaluation and taking the principle of “avoiding risk and reducing MPD cost”, combined with the accurate ECD calculation method considering multiphase flow, this paper puts forward the accurate determination method of matching the stratum interval of MPD, which can reduce the section of MPD construction as much as possible and optimize the casing level on the premise of ensuring safety. Based on the artificial bee colony algorithm, the intelligent determination method of casing level and setting depth under the condition of pressure control is established, which can quickly and accurately obtain the maximum casing setting depth and its corresponding optimal pressure control parameters in the open-hole section. The case analysis shows that, compared with the conventional drilling mode, the “upper conventional + lower MPD” drilling method can save one layer of casing while ensuring safety. The proposed method can provide theoretical and scientific basis for the accurate calculation of MPD matching stratum interval under the “conventional + MPD” compound drilling mode and the scientific and efficient design of casing levels and setting depth under the condition of pressure control.